Warm in 2008 Versus Cold in 2022? A Comparison of China-Related News in the US Media During the Beijing Summer and Winter Olympic Games - Xianwen Kuang (Journal of Current Chinese Affairs)
This study investigates the evolution of American news reports on China hosting the 2008 Summer and 2022 Winter Olympic Games, within the context of changing China–US relations. Existing studies on media coverage of the Beijing Olympics typically focus on either the Summer or the Winter Games individually, with none exploring the specific associations between bilateral relations and the agenda-setting processes of the US news media. To fill the gap, the study conducts a quantitative content analysis on reports from seven influential US news organisations which have covered issues in China during both Beijing Olympic Games. Findings reveal a marked increase in politicisation and negative sentiment in US news reports on China in 2022 compared to 2008. This suggests a strong correlation between the evolving China–US relations and the selection of news agendas and tones by US media.